2019
DOI: 10.4012/dmj.2018-111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage and aging conditions on the flexural strength and flexural modulus of CAD/CAM materials

Abstract: Computer-aided design/computer-aided manufacturing (CAD/CAM) materials were submitted to thermocycling, to identify changes in mechanical behavior. Four CAD/CAM materials were divided in four subordinate groups (n=9): (1) dry out for 7 days, (2) distilled water at 37 o C for 7 days, (3) 60,000 thermocycles, and (4) 120,000 thermocycles. Following thermocycling, samples were submitted to three-point bending test. Two-way ANOVA and post-hoc Tukey's test were performed (α=0.05). The IPS e.max CAD had a flexural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
(56 reference statements)
2
21
0
1
Order By: Relevance
“…This can be supported by the SEM images presented by Kang et al (2013) (1) , showing initially similar crystalline patterns in IPS e.max CAD and Rosetta SM, yet following crystallization; more dense crystalline microstructure was formed with crystal size increased up to 2-3μm for IPS e.max CAD while 1-2μm for the Rosetta SM. Also, Porto et al (2019) (32) , recorded rough surface of IPS e.max CAD with peaks and valleys, with cracks and hackles in small areas. They also found that CAD/CAM ceramics were not affected by aging and performed better after hydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be supported by the SEM images presented by Kang et al (2013) (1) , showing initially similar crystalline patterns in IPS e.max CAD and Rosetta SM, yet following crystallization; more dense crystalline microstructure was formed with crystal size increased up to 2-3μm for IPS e.max CAD while 1-2μm for the Rosetta SM. Also, Porto et al (2019) (32) , recorded rough surface of IPS e.max CAD with peaks and valleys, with cracks and hackles in small areas. They also found that CAD/CAM ceramics were not affected by aging and performed better after hydration.…”
Section: Discussionmentioning
confidence: 99%
“…Heat treatment, base glass composition, and nucleating agents greatly affects crystals' size among different factors (44) . Also, some researchers concluded that thermal stressing may cause tensions within the material which consequently slows down crack growth (32,45) .…”
Section: Discussionmentioning
confidence: 99%
“…the failure of a material subjected to stresses or deformations over a period of time [15]. The composition and the conformation of each ceramic confers to its mechanical properties, which can favor or hinder the development of factures by fatigue [18] (chart 5).…”
Section: Composition and Failure About Cad/cam Ceramicsmentioning
confidence: 99%
“…Some examples of ceramics in this condition are: lithium disilicate glass-ceramic (IPS e.max Press or CAD by Ivoclar-Vivadent), fine-grained zirconia (e.g. Lava Plus from 3M ESPE, Bruxzir from Glidewell, Allzir from New Image) and surface-infiltrated glass (chart 6) [15,18,19].…”
Section: Composition and Failure About Cad/cam Ceramicsmentioning
confidence: 99%
“…(2) This ceramic material meets the esthetic requirements and represents an economic alternative to ZrO 2 -supported single tooth restorations. (3) According to the manufacturer, it can be cemented by use of the adhesive, self-adhesive or conventional techniques. This later technique can be used with glass ionomer cement.…”
Section: Introductionmentioning
confidence: 99%